Improved Spectral Efficiency in Uplink Multicell Massive MIMO Cellular Communication Systems Using MMSE Channel Estimation and ZF Uplink Combining - Rajeev Kumar Shakya; Yibeltal Abebaw; Demissie Jobir Gelmecha; Eshetu Tessema Ware (Theory and Applications of Engineering Research Vol. 2, 2024)
In this chapter, we consider the multi-user multiple input multiple outputs (MU-MIMO) and SE performance analysis is presented against pilot contamination mitigation with different parameters. The maximum area throughput limit of a multi-cell Massive MIMO system can be reached by increasing bandwidth, cell density, and spectral efficiency. The Spectral efficiency (SE), which makes use of the linear Zero Forcing uplink combining method, can be modeled under the rician fading channel in order to assess the area throughput for such scenarios. In the case of uplinks, the BS is in charge of channel estimation. Different from existing work, the proposed model incorporates various estimators such as Minimum Mean Square Error (MMSE), Element-Wise Minimum Mean Square Error estimators under rician fading. The multi-cell scenarios with uplink (UL) massive MIMO has been analyzed using the proposed model under different cases such as pilot reuse factor, coherence block length, different number of antennas and different estimators. Based on these parameters, the analysis and outcomes of the simulation are presented. It is discovered that employing an efficient pilot reuse factor, building multiple BS antennas, servicing multiple numbers of UEs per cell, and optimizing MMSE channel estimation utilizing ZF UL combiner can all improve the average summation of SE per cell. The MMSE and ZF uplink combining are found to more suitable in improving SE as compared to MMSE-MR. For examples, the uplink SE of MMSE channel estimator for pilot reuse factors,1,3,4 is calculated as 22.5 bit/s/Hz/cell, 22.3 bit/s/Hz/cell and 21 bit/s/Hz/cell respectively. The uplink SE for EW-MMSE channel estimator with pilot reuse factors, 1, 3, 4 is calculated as 22.5bit/s/Hz/cell, 22 bit/s/Hz/cell and 22 bit/s/Hz/cell respectively. For the uplink SE of LS channel estimators, it can be 17.9bit/s/Hz/cell, 20.2 bit/s/Hz/cell, 20bit/s/Hz/cell with pilot reuse factors as f = 1, 3, 4 respectively. So, for f=3, the maximum calculated uplink SE for MMSE, EW-MMSE and LS is 17.6 bit/s/Hz/cell, 17.8bit/s/Hz/cell and 13bit/s/Hz/cell respectively. There is not much effect on coherence block as when it increases then the SE increases as well. It is also observed based on results that the ZF uplink combining technique can suppress the coherence interference and hence the average sum SE is enhanced with MMSE channel estimator and a pilot reuse factor of f=3 with ZF uplink combining. There is also trade-off between the pilot contamination mitigation and the larger SE. However, there is not much effect on coherence block as when it increases then the SE increases as well.